2012
DOI: 10.2105/ajph.2011.300433
|View full text |Cite
|
Sign up to set email alerts
|

Syndemic Theory and HIV-Related Risk Among Young Transgender Women: The Role of Multiple, Co-Occurring Health Problems and Social Marginalization

Abstract: Objectives. We assessed whether multiple psychosocial factors are additive in their relationship to sexual risk behavior and self-reported HIV status (i.e., can be characterized as a syndemic) among young transgender women and the relationship of indicators of social marginalization to psychosocial factors. Methods. Participants (n = 151) were aged 15 to 24 years and lived in Chicago or Los Angeles. We collected data on psychosocial factors (low self-esteem, polysubstance use, victimization related to transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
282
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(305 citation statements)
references
References 28 publications
16
282
3
4
Order By: Relevance
“…For example, previous studies have found that high rates of discrimination and victimization predicted unsafe sexual practices among transgender women (Brennan et al 2012;Garofalo et al 2007). Singer and colleagues (2006) describe many of the structural features of VDH, and argue that multiple inequalities contribute to the syndemic of "substance abuse, violence, and AIDS" (SAVA) among socially marginalized groups.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous studies have found that high rates of discrimination and victimization predicted unsafe sexual practices among transgender women (Brennan et al 2012;Garofalo et al 2007). Singer and colleagues (2006) describe many of the structural features of VDH, and argue that multiple inequalities contribute to the syndemic of "substance abuse, violence, and AIDS" (SAVA) among socially marginalized groups.…”
Section: Introductionmentioning
confidence: 99%
“…13 Several factors may place transgender women at a higher risk of psychological distress than transgender men, such as greater difficulty blending into society (also known as ''passing'') and experiencing higher levels of genderbased stigmatization and forms of discrimination. 13 These include gender abuse, such as verbal assaults or physical abuse, 11,22 intimate partner violence, 45 and physical or sexual assaults (38%-50%) that might be frequently targeted toward transgender women. 10,11,22 Other factors include a high prevalence sex work as a main economic activity (64%-67%) in samples of transgender women, 45,46 and a high prevalence of sexual risk behaviors among this population.…”
Section: Stigma and Mental Health Among Transgender Womenmentioning
confidence: 99%
“…13 These include gender abuse, such as verbal assaults or physical abuse, 11,22 intimate partner violence, 45 and physical or sexual assaults (38%-50%) that might be frequently targeted toward transgender women. 10,11,22 Other factors include a high prevalence sex work as a main economic activity (64%-67%) in samples of transgender women, 45,46 and a high prevalence of sexual risk behaviors among this population. Past studies also found that transgender women are more likely to report unstable housing and low income than transgender men.…”
Section: Stigma and Mental Health Among Transgender Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…2 This population experiences high levels of stigma, violence, depression, sex work, and substance use that make them particularly vulnerable to HIV infection. 3 Recent evidence from cross-sectional and qualitative studies suggests disparities in engagement and retention in care among transgender women compared to other people living with HIV. 4 However, data on clinical outcomes among the HIV-infected transgender women are very limited.…”
mentioning
confidence: 99%